2010
DOI: 10.1007/s11682-010-9102-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreased prefrontal cortex activity in mild traumatic brain injury during performance of an auditory oddball task

Abstract: Up to one-third of patients with mild traumatic brain injury (TBI) demonstrate persistent cognitive deficits in the 'executive' function domain. Mild TBI patients have shown prefrontal cortex activity deficits during the performance of executive tasks requiring active information maintenance and manipulation. However, it is unclear whether these deficits are related to the executive processes themselves, or to the degree of mental effort. To determine whether prefrontal deficits also would be found during less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
74
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 106 publications
5
74
1
1
Order By: Relevance
“…The network of temporoparietal, temporal, cerebellar, thalamic and frontal regions shown to be associated with task performance is consistent with similar oddball-type selective attention tasks studied previously (Kiehl and Liddle, 2001; Kiehl et al, 2005; Linden et al, 1999; Witt et al, 2010; Wolf et al, 2008). Also consistent with previous studies of oddball tasks, the temporoparietal junction showed the strongest response during the task in silence in healthy subjects.…”
Section: Discussionsupporting
confidence: 87%
“…The network of temporoparietal, temporal, cerebellar, thalamic and frontal regions shown to be associated with task performance is consistent with similar oddball-type selective attention tasks studied previously (Kiehl and Liddle, 2001; Kiehl et al, 2005; Linden et al, 1999; Witt et al, 2010; Wolf et al, 2008). Also consistent with previous studies of oddball tasks, the temporoparietal junction showed the strongest response during the task in silence in healthy subjects.…”
Section: Discussionsupporting
confidence: 87%
“…55,57,58 Further, reduced functional connectivity in concussed persons has been observed during attention and working memory paradigms. 80,81 In addition, recent functional magnetic resonance imaging 82 demonstrated activation deficits during performance of an oddball task in the dorsolateral prefrontal cortex and superior parietal lobe in formerly concussed persons. Hence, concussive injuries may disrupt the structural or functional integrity of areas responsible for P3 generation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Talavage and colleagues (2010) reported hypoactivation in concussed adolescent football players within the left middle and superior temporal gyri, left middle occipital gyrus, and bilateral cerebellum, during an N-back working memory task. Similarly, adult fMRI studies of semi-acute mTBI have also reported a mixture of both hypoactivation (Mayer et al, 2009;McAllister et al, 1999McAllister et al, ,2001Witt et al, 2010), and hyperactivation (McAllister et al, 1999(McAllister et al, ,2001Slobounov et al, 2010;Smits et al, 2009), during a variety of different cognitive challenges.…”
Section: Introductionmentioning
confidence: 93%